Genetic polymorphism of merozoite surface protein-1 and merozoite surface protein-2 in Plasmodium falciparum isolates from Brazzaville, Republic of Congo - Malonga Freddy; Ndounga Mathieu; Mayengue Pembe; Bitemo Michel; Ntoumi Francine (Malaria Journal, 2011)
Abstract Background The characterization of malaria parasite populations circulating in an area is part of site characterization, as a basis for evaluating the impact of malaria interventions on genetic diversity, parasite species, and multiplicity of infection. The present study was aimed at analysing genetic diversity of Plasmodium falciparum merozoite surface proteins 1 and 2 (MSP-1 and MSP-2) and to determine the multiplicity of infection in clinical isolates collected from children living in the Southern district of Brazzaville in the Republic of Congo. Methods A total of 125 isolates from patients with uncomplicated malaria attending Terinkyo and Madibou health centres were collected between January and June 2005 while evaluating the therapeutic efficacy of amodiaquine-artesunate combination. DNA was extracted and msp-1 and msp-2 genes were genotyped using allele-specific nested-PCR. Results Out of 468 distinct fragments detected, 15 msp-1 and 20 msp-2 genotypes were identified. For the msp-1 gene, K1 family was the predominant allelic type carried alone or in association with RO33 and Mad20 types, whereas the 3D7 family was the most prevalent in the msp-2 gene. Overall, the mean multiplicity of infection was 2.2. Out of 125 samples, 104 (83%) harboured more than one parasite genotype. There was no statistical significant difference in the multiplicity of infection by either sex or age of patients. However, a statistically significant correlation was found between parasite densities and the number of genotypes. Conclusion Polymorphism in P. falciparum clinical isolates from Brazzaville was high and mainly of multiple clones. The basis for the positive association between parasite densities and multiplicity of infection is discussed.